Angioarchitecture and Treatment Modalities in Posttraumatic Carotid Cavernous Fistulae - Malan, J. (Centauro S.r.l., 2012)
Posttraumatic carotid cavernous fistulae are abnormal direct hole communications between the intracavernous carotid artery and the cavernous sinus that can result from both blunt and penetrating trauma. They can be challenging lesions to treat and a variety of modalities and approaches have been proposed since endovascular treatment has become the standard treatment. An analysis of the angioarchitecture of 32 consecutive patients treated in our service demonstrated that seven could be classified as small hole, eight medium and 17 large. Different size fistulae required varying endovascular tools. Small fistulae were best treated using coils and large and medium lesions with balloons. Large lesions were more likely to require multiple tools in order to achieve closure and had a lower chance of ipsilateral carotid preservation. All patients in the series were cured with a carotid preservation rate of 66%. There was no permanent morbidity associated with endovascular treatment.